A novel optical strategy for ALP detection and development of matched smartphone app - Jiawei Li; Yi Cheng; Yingchun Huang; Lixin Xu; Kun Zhang; Fei Yan; Jian Chen; Chunhui Lang (Scientific Reports)
Abstract Alkaline phosphatase (ALP) is a reliable biomarker for various diseases, making the development of new detection methods highly significant. Herein, we report a simple and accurate dual-signal optical detection strategy for measuring ALP activity across the entire clinical range in adults. Based on this, we designed a smartphone app to eliminate the limitations of large instruments, enabling real-time field detection. In this work, ALP catalyzes the conversion of the phosphate monoester of 2-phospho-L-ascorbic acid (PAA) into ascorbic acid (AA), a compound with strong reducing properties. AA facilitates the in-situ reduction of Ag+ to form Au@Ag core-shell nanoparticles, accompanied by significant changes in the ultraviolet-visible absorption spectra and color. These changes allow for the qualitative and quantitative detection of ALP activity. In UV absorption spectroscopy and colorimetric detection, the signal shows good linearity with ALP activity concentrations, with detection ranges of 0 U/L to 200 U/L (R2=0.9961) and 25 U/L to 250 U/L (R2=0.9771), respectively. Subsequent selective analysis and serum sample analysis demonstrated the high selectivity and accuracy of the proposed method, highlighting its potential for field application.